Proposta de melhorias na sinalização de trânsito de pontos turísticos de Ibiúna-SP - Yoshizumi, Wiliam Massao (Universidade Federal de São Carlos, 2023)
As technology advances, transportation has become more accessible and efficient, turning long and tiresome journeys into more feasible routes for the general population. This has led to a substantial increase in people's movement across different parts of the world and subsequently, a surge in demand for tourist destinations. Among the many municipalities designated as Tourist Resorts in the São Paulo state, Ibiúna stands out, with tourism being a key economic driver. Alongside the attractions themselves, providing visitors with a positive experience necessitates a robust infrastructure encompassing accommodations, security, services, and other amenities. Consequently, the importance of appropriate traffic signage for these tourist spots cannot be overstated. This study aims to evaluate the indicative and tourist-oriented signage in Ibiúna, seeking to contribute to the city's tourism enhancement. Guided by the Brazilian Tourist Signage Guide, a field study was conducted to appraise the quality of traffic signage at the municipality's principal tourist attractions. The evaluation encompassed their adherence to stipulated standards and their effectiveness in guiding tourists towards an enjoyable experience. Despite generally well-structured and informative signage, notable deficiencies were identified in distance indication markers, along with the imperative of devising a maintenance plan for the existing signage. This demonstrates that Ibiúna municipality has recognized the importance of tourist traffic signage, with only a few minor improvements noted that could enhance the quality of the municipality's signage.
Proposal for improvements in traffic signs at tourist points in Ibiúna – SP
Keywords: Sinalização; Turismo; Ibiúna; Atrativos turísticos; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES